A) ((½)¹⁷ × 2⁶⁴) ÷ 2³⁵ = ?
b) ((x⁶)³ × x⁰) ÷ (x²)⁵ = ?
c) (4¹⁸ × 2²² × 8¹⁰) ÷ pierwiastek z 2 = ?

w punkcie c) wynik zapisz w postaci potęgi o podstawie 2

d) 3pierwiastki z 18 - pierwiastek z 72 + 2pierwiastki z 50 = ?
e) 3⁰ × 5-² × 8⅓ = ?

2

Odpowiedzi

2009-11-28T16:39:45+01:00
A) ((½)¹⁷ × 2⁶⁴) ÷ 2³⁵ = 2⁻¹⁷ × 2⁶⁴ ÷ 2³⁵ = 2⁶⁴⁻¹⁷⁻³⁵ = 2¹²
b) ((x⁶)³ × x⁰) ÷ (x²)⁵ = x¹⁸ × x⁰ ÷ x¹⁰ = x⁸
c) (4¹⁸ × 2²² × 8¹⁰) ÷ √2 = 2³⁶ × 2²² × 2³⁰ ÷ 2do potęgi½ = 2 do potegi 87½
d) 3√18 - √72 + 2√50 = 9√2 - 6√2 +10√2 = 13√2
e) 3⁰ × 5-² × 8⅓ = 1 × ⅕ × ³√8 = ⅕ × 2 = ⅖
1 5 1
Najlepsza Odpowiedź!
2009-11-28T16:50:46+01:00
A) ((½)¹⁷ × 2⁶⁴) ÷ 2³⁵ = ?
=[ (2 )⁻¹⁷ *2⁶⁴] : 2³⁵ =
= 2⁴⁷ : 2⁵ = 2¹²


b) ((x⁶)³ × x⁰) ÷ (x²)⁵ = ?
(x¹⁸*1) : x¹° = x¹⁸ : x¹° = x⁸

c) (4¹⁸ × 2²² × 8¹⁰) ÷ pierwiastek z 2 = ?
=[ (2²)¹⁸ *2²² *(2³)¹⁰ ] : √2=
=[ 2³⁶*2²² *2³⁰] :√2=
= 2⁸⁸ : √2 = √2*√2*2⁸⁷ : √2 = √2*2⁸⁷

w punkcie c) wynik zapisz w postaci potęgi o podstawie 2

d) 3pierwiastki z 18 - pierwiastek z 72 + 2pierwiastki z 50 = ?
= 3√18 -√72 +2√50=
= 3*√9*√2 -√36*√2 + 2*√25*√2=
=3*3√2 -6√2 + 2*5√2 =
= 9√2 -6√2 + 10√2=
= 13√2

e) 3⁰ × 5-² × 8⅓ = ?
=3° *5⁻² *(25/3)=
= 1*(1/25)*(25/3) = 1/3
1 5 1